2022
DOI: 10.1055/s-0042-1749441
|View full text |Cite
|
Sign up to set email alerts
|

Platelet Activation and Thrombosis in COVID-19

Abstract: Although thrombosis frequently occurs in infectious diseases, the coagulopathy associated with COVID-19 has unique characteristics. Compared with bacterial sepsis, COVID-19-associated coagulopathy presents with minimal changes in platelet counts, normal prothrombin times, and increased D-dimer and fibrinogen levels. These differences can be explained by the distinct pathophysiology of the thromboinflammatory responses. In sepsis-induced coagulopathy, leukocytes are primarily responsible for the coagulopathy by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
38
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(39 citation statements)
references
References 66 publications
0
38
0
1
Order By: Relevance
“…Enrichment analysis indicated that the overlapped genes were primarily associated with platelet activation, signaling and aggregation. Indeed, other studies showed the COVID-19 disease to be associated with platelet activation and increased platelet alpha granule secretion, which are critical in developing thrombosis in those patients 11,12 . Previous research found enhanced p-selectin and CD36 expression, markers of platelet alpha and dense granule secretion respectively, in COVID-19 patients compared to healthy controls, and this phenomenon was more evident in patients admitted to ICU versus common patients 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Enrichment analysis indicated that the overlapped genes were primarily associated with platelet activation, signaling and aggregation. Indeed, other studies showed the COVID-19 disease to be associated with platelet activation and increased platelet alpha granule secretion, which are critical in developing thrombosis in those patients 11,12 . Previous research found enhanced p-selectin and CD36 expression, markers of platelet alpha and dense granule secretion respectively, in COVID-19 patients compared to healthy controls, and this phenomenon was more evident in patients admitted to ICU versus common patients 13 .…”
Section: Discussionmentioning
confidence: 99%
“…45 46 SARS-CoV-2 can modify the platelet function and antithrombotic property of vascular endothelium to prothrombotic by binding to angiotensin-converting enzyme 2 (ACE2) on the cellular surface, and these changes can be the predominant causes of thrombosis in COVID-19. 18 Endotheliopathy is induced via the binding of SARS-CoV-2 to ACE2 on endothelial cells. Suppressed regulation of type I interferon and the decreased major histocompatibility complex class II–related activity due to the explosive replication of causative viruses in dendritic cells and macrophages are reported.…”
Section: Thrombosis-type Disseminated Intravascular Coagulationmentioning
confidence: 99%
“…For example, readily available coagulation tests, including D-dimer and prothrombin time, represent critical components of sepsis-associated DIC, but are only mild to moderately altered in COVID-19-associated coagulopathy, likely due to specific activation in the lung microcirculation and systemic coagulation activation being less significant. 18 Despite distinctly different pathogenesis, both diseases can progress to microthrombosis. The question often asked is COVID-19-associated coagulopathy DIC.…”
Section: Disseminated Intravascular Coagulation In the Pastmentioning
confidence: 99%
“…Moreover, the increase in the activity of VWF correlates with the severity of the disease, which indirectly reflects the degree of activation of platelets. VWF also plays a role in secondary hemostasis, i.e., it protects coagulation factor VIII against proteolysis via active protein C. In the course of COVID-19, factor VIII activity also intensifies, becoming another component of the hypercoagulable state [ 77 ].…”
Section: Coagulation Processes In Pneumonia Caused By Sars-cov-2 Infe...mentioning
confidence: 99%